Data-driven cleaner production strategy for energy-intensive manufacturing industries: Case studies from Southern and Northern China. (August 2022) - Ma, Shuaiyin; Zhang, Yingfeng; Lv, Jingxiang; Ren, Shan; Yang, Haidong; Wang, Chao
Highlights: A data-driven cleaner production strategy is proposed for energy-intensive industries. The data-driven strategy is explained by the cleaner production data lifecycle. The implementation models are developed to illustrate the proposed strategy. The effectiveness of the proposed strategy is discussed for companies in China. Abstract: Cleaner production is an effective strategy for improving material utilization, reducing energy consumption, maximizing product output, and minimizing emissions during the entire manufacturing processes. An increasing number of enterprises promote the implementation of cleaner production. In the Industry 4.0 context, product-embedded information devices are widely used to capture product lifecycle data. Product lifecycle management provides an opportunity to achieve cleaner production strategy. This paper presents a data-driven cleaner production strategy by product lifecycle management for energy-intensive manufacturing industries. The data-driven strategy is proposed and explained by the lifecycle of cleaner production data. Implementation models are developed to illustrate the proposed data-driven cleaner production strategy. Furthermore, two case studies from Southern and Northern China are presented to demonstrate the strategy. Results show that the unit energy consumption and the energy cost of production in Company A are reduced by at least 3% after applying the proposed strategy. In addition, the "cradle-to-gate" lifecycle data analysis indicates that the costs of environmental pollution in Company B are diminished significantly. Finally, energy-intensive manufacturing companies in China are compared and evaluated, and the effectiveness of the proposed strategy is discussed.